Advances in Design for Inclusion Proceedings of the AHFE 2018 International Conference on Design for Inclusion, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Di Bucchianico, Giuseppe (Advances in Intelligent Systems and Computing,, 2019)
This book addresses a range of topics in design, such as universal design, design for all, digital inclusion, universal usability, and accessibility of technologies for people regardless of their age, financial situation, education, geographic location, culture and language. It especially focuses on accessibility for people with auditory, cognitive, neurological, and visual impairments, ageing populations, and mobility for those with special physical needs. The book explores some of the overlaps between inclusive design and web accessibility to help managers, designers, developers, policy makers, and researchers optimize their efforts in these areas. Based on the AHFE 2018 International Conference on Design for Inclusion, held on July 21-25, 2018, in Orlando, Florida, USA, it discusses new design technologies and highlights the disparate needs of the individuals within a community. Thanks to its multidisciplinary approach, it is a valuable resource for readers from various backgrounds, providing them a timely, practice-oriented guide to design for inclusion.